PEMBAHARUAN PENDIDIKAN PERSPEKTIF AHMAD DAHLAN - Erjati Abbas (Pascasarjana IAIN Metro, 2020)
The Islamic reform movement in Indonesia cannot be separated from the figure of Ahmad Dahlan through the Muhammadiyah organization. This can be traced through the early history and development of Muhammadiyah which was shown by Ahmad Dahlan's character through the idea of renewal or the tajdid movement. This article looks at the character of KH. Ahmad Dahlan from an anthropological and sociological perspective. The reading is intended to determine the role of the character in the map of the development of the community. The main thing to be examined in this article is the correlation between KH. Ahmad Dahlan and the pesantren education system in Indonesia. The correlation between Muhammadiyah and Islamic boarding schools was studied using the discussion of the categorical simplification model on three indicators of Muhammadiyah's function and role, namely as an educational institution and the development of Islamic teachings, as an institution for Islamic struggle and da'wah, and as an institution for community empowerment and service. From the three categories it can be seen that KH. Ahmad Dahlan is a figure who is able to respond to the latest challenges quickly and precisely through the tajdid (renewal) movement in the fields of education, preaching, and empowering the Indonesian people.